AB0473 Evaluation of anti-TNF levels and anti-TNF antibodies in rheumatic diseases treated with infliximab and adalimumab; results from a local registry. (23rd January 2014) - Rosas, J.; Llinares-Tello, F.; Senabre, J.M.; Santos-Ramírez, C.; Santos-Soler, G.; Salas, E.; Barber, X.; Sánchez-Barrioluengo, M.; Molina-García, J.; Llahí, N.; Cano, C.
Abstract : Objectives: To analyse the clinical relevance of serum levels of infliximab (INF) and adalimumab (ADA) and the production of anti-INF (INF-Abs) or anti-ADA antibodies (ADA-Abs) from a local registry of patients with rheumatic diseases on treatment with INF or ADA. Methods: We included 74 consecutive patients receiving treatment for more than 6 months with INF (31 tests in 25 patients) and ADA (56 test in 49 patients). Clinical characteristics, clinical activity index (DAS in 28 joints for rheumatoid arthritis -RA- and psoriatic arthritis -PsA-; BASFI, BASDAI for ankylosing spondylitis -AE-) were recorded. Serum levels of INF or ADA and INF-Abs or ADA-Abs (ELISA kit. Promonitor®-INF, ADA. Proteomika, Derio. Vizcaya. Spain) were evaluated. Cut-off level for serum Abs for INF was >37 U/mL, and for ADA >8 U/mL and cut-off level for serum level of INF and ADA were <0.04 mg/L and <0.002 mg/L respectively. Serum samples were collected at the time of infusion of INF or before injection of ADA, and stored frozen until analysis. Infusion reactions with INF were defined as any event appearing during infusion requiring either arrest of drug infusion or the administration of parenteral medication. Patients were considered responders if they had at the same time of extraction, DAS28-ESR≤3 in RA or PsA patients; BASDAI≤4 in AE patients. Results: We enrolled 74 patients, 50 (68%) were women; the mean age was 54±15years (range: 16-78 years). The diagnosis of patients was: RA (47%), AE (30%), PsA (12%) and others (11%). The average time of treatment for the whole population was 31±22 months (mean; 27 months): for INF group: 43.7 months (median: 42, range: 6-127) and for ADA: 23.9 months (median: 21; range: 6-51). INF was the first anti-TNF received in 24 (96%) of the patients, and ADA was the first in 37 (76%) of the patients. Antibodies were detected in 9/74 patients (12%): 4/25 patients (16%) INF-Abs and 5/49 patients (10%) ADA-Abs. In the INF-Abs and ADA-Abs patients: all of them had low level of INF or ADA respectively, with a range level of Abs for INF between 67-121.849 U/mL and for ADA between 132-717.824 U/mL. Three patients had infusion reaction with INF, all of them with high level of Abs (61, 1.282, 121.849 U/mL). Table 1 showed the characteristics in responders and non-responders patients. Conclusions: 1. Serum antibodies were detected in 16% of patients receiving treatment with INF and 10% of patients with ADA. 2. Patients responders have absence of Abs and significantly higher serum concentrations of anti-TNF than non-responders. 3. Immunogenicity can induce inefficacy in patients on treatment with anti-TNF. Disclosure of Interest: J. Rosas Grant/Research support from: Asociaciόn para la Investigaciόn en Reumatología de la Marina Baixa (AIRE-MB), F. Llinares-Tello: None Declared, J. M. Senabre: None Declared, C. Santos-Ramírez: None Declared, G. Santos-Soler: None Declared, E. Salas: None Declared, X. Barber: None Declared, M. Sánchez-Barrioluengo: None Declared, J. Molina-García: None Declared, N. Llahí: None Declared, C. Cano: None Declared